PROFIL PENGEMBANGAN TANAMAN PANGAN DI KABUPATEN CILACAP JAWA TENGAH - E, Adwi Herry K.; Tobari, Tobari (Jenderal Soedirman University, 2008)
Pembangunan sektor pertanian harus mampu memanfaatkan keunggulan komparatif dari setiap wilayahyang berbeda, sehingga mampu memberikan dampak ekonomi pada wilayah tersebut. Penelitian bertujuan untukmempelajari wilayah yang berpotensi memiliki komoditas basis tanaman pangan yang bersifat spesifik danmemiliki unggulan pasar, sebaran masing-masing komoditas tanaman pangan di wilayah yang bersangkutan,surplus produksi atau pendapatan komoditas basis tanaman pangan di setiap wilayah, pengaruh efek penggandaproduksi atau pendapatan komoditas basis tanaman pangan terhadap peningkatan produksi atau pendapatankomoditas non basis, dan Tingkat pertumbuhan komoditas basis tanaman pangan. Hasil penelitian menunjukkan:(1) Terdapat 6 komoditas basis tanaman pangan di Kabupaten Cilacap yaitu padi sawah, jagung, kedelai, kacanghijau, kacang tanah, dan ubi kayu, (2) Menurut lokalisasinya budidaya komoditas tanaman pangan cenderungmenyebar tidak merata, dan tidak ada satupun wilayah kecamatan yang melakukan spesialisasi pada komoditastanaman pangan tertentu, (3) Surplus produksi setiap wilayah kecamatan ada yang bernilai positif dan negatif,tetapi hampir semua komoditas basis memberikan kontribusi yang besar terhadap surplus di tingkat wilayahkecamatan, (4) Nilai efek pengganda produksi terbesar adalah Kecamatan Cipari, Karangpucung, dan KecamatanKawunganten dan (5) Hampir semua komoditas tanaman pangan mengalami pertumbuhan pesat dan secaraumum 8 komoditas basis yang ada menjadi komoditas andalan di masing-masing Kecamatan di KabupatenCilacap.Kata kunci: tanaman pangan, keunggulan komperatif, kabupaten CilacapABSTRACTDevelopment agricultural sector have to able to exploit the comparability excellence from each everydifferent region, so that able to give the economic impact at the region. Agriculture represent the especialactivator of economic development of national. The mentioned caused agriculture able to create the economicgrowth, make-up of foreign exchange, development of food resilience, continuation of environment, opportunityextension work and try, and also economic development acceleration generalization [of] area. Therefore,rebuilding Indonesia economics of agriculture area precisely and realistic (Saragih,1999). Developmentagricultural sector of intensification program ekspanding, rehabilitate, up to diversified also the included inpriority category to be developed, besides industrial area development and service. The mentioned by product toagricultural produce can be instructed better so that able to compete [in] international and also local market. Thisresearch aimed to determine the region which have potency own the commodity of bases of food crop having thecharacter of specific and own to exeed the market, swampy forest of each commodity of food crop in pertinentregion, surplus produce or earnings of commodity of bases of food crop in each every region, influence of effectmultiplyer produce or earnings of commodity of bases of food crop to product increase or commodity earningsof[is non bases, and Mount the growth of commodity of bases of food crop. Result of research menunjukan that:(1) There are 6 commodity of bases of food crop [in] Regency Cilacap that is rice field paddy, maize, soy, greenpeanut, peanut, and cassava, ( 2) According to its localization [is] budidaya of commodity of food crop tend to todisseminate do not flatten, and there no regional of subdistrict conducting specialization of at certain food cropcommodity, (3) Surplus produce each;every subdistrict region there [is] negative and positive valuable, but mostof all bases commodity give the big contribution to surplus in regional storey level of subdistrict (4) Value ofbiggest effect pengganda production be subdistrict Cipari, Karangpucung, and Subdistrict Kawunganten and (5)Most of all commodity of food crop experience of the fast growth in Regency Cilacap, and in general 8 existingbases commodity become the pledge commodity in each subdistrict of exist in Regency CilacapKey words: area, food crops, comparativeness, Cilacap District